Microstructured transparent conductive metallic electrodes fabricated by colloidal lithography - Luis, João Sousa (2018)
This thesis focuses on the development and optimization of a technique known as self-assembly colloidal lithography (CL) to fabricate transparent conductive electrodes. These contacts are of utmost importance for high performance optoelectronic devices, such as thin film solar cells. As of this moment, indium tin oxide (ITO) is the preferred transparent conductive oxide (TCO), but to improve the cell efficiency new materials with lower sheet resistance and better optical properties should be used. Besides, ITO is relatively expensive, so alternative Earth-abundant materials are highly desired to improve the devices’ cost-effectiveness. Conductive metallic micro-meshes within two thin TCO layers were investigated to improve the sheet resistance while maintaining an anti-reflection coating (ARC) type layer. The meshes were fabricated by CL after studying the influence of the main process parameters: polystyrene sphere sizes, etching times, aluminum and silver for the mesh and indium zinc oxide (IZO) and aluminum zinc oxide (AZO) for the TCO layer were studied. The resulting contacts were analyzed through UV-VIS-NIR spectrophotometry, hall-effect, scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS) and atomic force microscopy (AFM). The results showed that 1.6 μm precursor spheres etched for 150s were the most reliable to produce closely-packed structures and to obtain low sheet resistance, while 5 μm spheres etched for 120s showed the best optical performance over the UV-VIS-NIR range. The contacts which showed the best optical and electrical results were produced with silver and IZO: when produced with 1.6 μm spheres the contacts presented sheet resistances as low as 10.6 Ω/sq and transmittances up to 75 %, and when produced with 5 μm spheres obtained transmittance up to 85 % with sheet resistance of 121 Ω/sq. The results reveal that our innovative large-area micro-meshed metallic electrodes fabricated by CL can attain performances close to those off state-of-art ITO (10 Ω/sq for 80 % transmittance and 100 Ω/sq for 90 % transmittance), but with superior transmittance mainly in the near-infrared range. This can be highly interesting, for instance, for the intermediate electrodes in multi-terminal multi-junction solar cell architectures.